The Incorporation of Lemon Grass (Cymbopogon citratus) Leaf Powder in Chicken Meat Ball: Influence on Nutritional Value, Sensory Attributes, Texture and Keeping Quality - Olayemi Rashidat Awodoyin (Turkish Journal of Agriculture: Food Science and Technology)
Processed chicken meat products are more susceptible to oxidative deterioration which reduces the quality and safety of the product, therefore, the need to include antioxidants during processing order delay its processes. Chicken meat (from live broiler birds procured from the Teaching and Research Farm, University of Ibadan) was ground through a 5 mm plate of a meat mincer. Ingredients such as red pepper, black pepper, garlic, onions, salt, refined vegetable oil (Grand soya oil®) ice flakes and Lemon Grass Leaf Powder (LGLP) were added and mixed thoroughly with chicken meat for homogeneity. There were four treatment groups: T1 = (0g LGLP), T2 = (2g LGLP), T3 = (4g LGLP), T4 = (6g LGLP). Each batch was oven cooked separately and replicated three times. Proximate composition (%), sensory characteristics (9-point hedonic scale), Thiobarbituric Acid Reactive Substances (TBARS MDAµg/g) were assessed and data generated were analysed using ANOVA @ P<0.05). Moisture 51.24 (6gLGLP) was significantly higher than 52.69 (4gLGLP), 53.04(2gLGLP) and 54.69 (0gLGLP); fat 16.09 (2gLGLP) is similar with 17.19 (4g LGLP) and lower than 15.89 (0gLGLP) but lower than 17.48 (6gLGLP) (P<0.05). Crude protein 19.52 (4gLGLP) is similar to 18.10 (2gLGLP) and 19.18 (6gLGLP) but significantly higher than 17.85 (0gLGLP). The hardness 2983.81kg (0gLGLP) and 3442.86kg (2gLGLP) were similar but lower than 5395.55kg (4gLGLP) and 5523.17kg (6gLGLP) (P>0.05). Chewiness 2790.83kg (0gLGLP) is not different from 3413.43kg (2gLGLP) and 5315.52 (4gLGLP) but higher (P<0.05) than 5523.10kg (6gLGLP) (P>0.05). No significant variation exists in the sensory characteristics among chicken meatballs. The TBARS 1.74 (6gLGLP) is lower than 1.80 (4gLGLP), 1.86 (2gLGLP) and 1.84 (0gLGLP). Utilisation of different levels of lemongrass leaf powder in chicken meat balls production increased the nutrition and improved the lipid oxidation stability of the product during refrigerated storage.